(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The new 2-arylquinoline-4-carboxylic acid derivatives 4(a-f) and 5(a-i), were tested by qualitative and quantitative methods on various bacterial and fungal strains and proved to be active at low concentrations against Gram-positive and Gram-negative bacteria as well as fungi. The MIC values were determined for test compounds as well as for reference standards. Compounds 4b and 5d showed better antibacterial and antifungal activity than clinically prevalent drugs (Gentamicin, Ampicillin and Fluconazole) against Staphylococcus aureus and Candida albicans. The structures of newly synthesized compounds have been characterized on the basis of their spectroscopic data. The study revealed the potential of newly synthesized compounds as a novel group of antimicrobials.